2017
DOI: 10.1089/ars.2017.7140
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cellular Redox Signaling by Matricellular Proteins in Vascular Biology, Immunology, and Cancer

Abstract: Significance: In contrast to structural elements of the extracellular matrix, matricellular proteins appear transiently during development and injury responses, but their sustained expression can contribute to chronic disease. Through interactions with other matrix components and specific cell surface receptors, matricellular proteins regulate multiple signaling pathways, including those mediated by reactive oxygen and nitrogen species and H 2 S. Dysregulation of matricellular proteins contributes to the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 319 publications
(370 reference statements)
0
24
0
Order By: Relevance
“…systems able to perpetuate the Chronicity of inflammation, and further acquisitions on cellularity (chemo-taxis, macrophages and monocytes) demonstrate their complex interconnection that makes it still difficult to univocally explain the processes involved respectively at the cellular level, intercellular and with the extracellular matrix [5][6][7]. Biofilms, ROS / NOS systems [8][9][10][11][12][13], microvesicles [14,15], metalloproteases [3][4][5] and other factors have been examined and are sometimes held responsible for the transformation of the acute inflammatory state into chronic [14][15][16][17][18][19][20]. Only the presence of the infection in bio film form and the ability of the latter to modify the host's reaction appear to be able to provide a plausible explanation, but not all ulcers are infected and not all are found of biofilm [21,22].…”
mentioning
confidence: 99%
“…systems able to perpetuate the Chronicity of inflammation, and further acquisitions on cellularity (chemo-taxis, macrophages and monocytes) demonstrate their complex interconnection that makes it still difficult to univocally explain the processes involved respectively at the cellular level, intercellular and with the extracellular matrix [5][6][7]. Biofilms, ROS / NOS systems [8][9][10][11][12][13], microvesicles [14,15], metalloproteases [3][4][5] and other factors have been examined and are sometimes held responsible for the transformation of the acute inflammatory state into chronic [14][15][16][17][18][19][20]. Only the presence of the infection in bio film form and the ability of the latter to modify the host's reaction appear to be able to provide a plausible explanation, but not all ulcers are infected and not all are found of biofilm [21,22].…”
mentioning
confidence: 99%
“…Hypoxia and fluid shear stress activate NOS3 to increase blood flow, and adrenergic tone opposes this vasodilator activity of NO to maintain physiological blood pressure. Studies using mice lacking thrombospondin-1 or CD47 demonstrated a physiological role for CD47 signaling to limit both NO biosynthesis and cGMP-mediated signaling pathways controlled by NO in the vasculature (9). Thrombospondin-1 accumulates in the vasculature in response to ischemic injuries and several chronic diseases of aging, thereby limiting NO signaling and tissue perfusion.…”
mentioning
confidence: 99%
“…Two articles in this Forum review physiological and Laboratory of Pathology, Center for Cancer Research, National Cancer Institute, National Institutes of Health, Bethesda, Maryland. pathophysiological functions of this pathway and the potential to therapeutically suppress CD47 signaling to restore NO signaling in acute ischemic injuries, cardiovascular disease, and aging (5,9).…”
mentioning
confidence: 99%
See 2 more Smart Citations